2021
DOI: 10.3846/jcem.2021.15252
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Fuzzy Multiple Criteria Decision Making Methods in Civil Engineering: A State-of-the-Art Survey

Abstract: A variety of fuzzy multiple criteria decision making (MCDM) models have been proposed to solve complicated decision-making problems. Many applications have been achieved, especially in the field of civil engineering. To analyze the developments about the fuzzy MCDM methods and their applications in civil engineering in recent years and further explore the future research directions, this study conducts a state of the art survey in which 52 journal papers focusing on the applications of fuzzy MCDM models in civ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2121
2121

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 70 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…Thus using this number of experts in decision-making articles is famous among scholars (e.g. Wen et al. , 2021; Amiri et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus using this number of experts in decision-making articles is famous among scholars (e.g. Wen et al. , 2021; Amiri et al.…”
Section: Methodsmentioning
confidence: 99%
“…Thus using this number of experts in decision-making articles is famous among scholars (e.g. Wen et al, 2021;Amiri et al, 2021). The expert profiles who took part in this study are included in Table 2.…”
Section: Phasementioning
confidence: 99%
“…Accordingly, the higher the understanding of the workers from the health of the environment, the higher the safety during the work can be [16,17]. If the workers know the health risk precisely, they could treat it more efficiently and take the proper measures to handle it [18]. Such safety can be achieved through different means, including the proper instruction of the workers, their higher knowledge (sub-criteria) of the work and the environment surrounding them, and the proper use of modern technology and facilities (sub-criteria) [19,20].…”
Section: Selection Of the Right Modelmentioning
confidence: 99%
“…Balali et al [93] applied the PROMETHEE method to the selection of materials and building techniques for the Kashkhan bridge, in Iran; Safa et al [94] developed an integrated construction materials management (ICMM) model through implementation on the TOPSIS (technique for order preference by similarity to ideal solution); Jiang et al [95] proposed to support the choice of various wireless technologies for tracking construction materials, using fuzzy decision making; Zavadskas et al [96] and Zavadskas et al [97] wrote pioneer papers regarding the use of the decision-making methods in the choice of building materials; Flórez et al [98] explored the impact of sustainability in an optimization model that can help decision makers to select materials; Jadid and Badrah [99] implemented a decision support system for materials information management for projects under construction by owners; Sefair et al [100] offered a multiple-criteria decision method to rank candidate materials in building construction, on the basis of their environmental impact, design, and cost; Littidej et al [101] applied an integrated multi-objective decision analysis (MODA) and a GIS method to choose the possible sites for building material delivery centers (DCs) in a municipality of Thailand; Primova et al [102] suggested an approach for optimizing the choice of construction material using nonlinear regression equations; Mathiyazhagan et al [103] selected materials on the basis of a sustainability concept using best-worst methodology (BWM) and a fuzzy TOPSIS approach; Krivogina et al [104] proposed a multi-criteria approach for the optimal control of the production of building materials. The applications of crisp and fuzzy multiple-criteria decision-making methods in construction, including the domain of building material selection, were reviewed by Wen et al [105].…”
Section: Materials Selection With Decision Approachesmentioning
confidence: 99%